De novo Lesions Frequently Develop in Adult Normal Thyroid Over Almost Six Years - Brigante, Giulia; Monzani, Maria Laura; Locaso, Michela; Gnarini, Valentina Luisa; Graziadei, Luigi; Kaleci, Shaniko; De Santis, Maria Cristina; Tagliavini, Simonetta; Simoni, Manuela; Rochira, Vincenzo; Madeo, Bruno (Frontiers in Endocrinology, 2020)
Purpose. In order to understand how thyroid abnormalities emerge over time in adults, we evaluated incidence of thyroid diseases in healthy subjects, after almost six years from a previous negative ultrasound. Methods. Anamnestic and physical data were collected. Ultrasound neck evaluation was performed by an experienced endocrinologist, recording detailed thyroid and nodules characteristics. Nodules were classified according to American Thyroid Association classification for prediction of cancer risk. Serum samples were collected for subsequent evaluations (TSH, free thyroid hormones, calcitonin, anti-thyroid antibodies). Anamnestic, clinical, sonographic and serological characteristics were analyzed with logistic regression analysis for subjects with nodules versus those without. Results. 111 subjects were enrolled (43M, 68F). Half of them developed nodules, mainly smaller than 1 cm and without suspicious characteristics. Ninety-seven percent were euthyroid. Only 4% had serological diagnosis of thyroiditis. Incidence of thyroid diseases was higher in women, especially nulliparous. Comparing clinical characteristics of subjects with and without nodules, the only statistically significant difference concerned thyroid volume adjusted for body weight or surface (p<0.05), but not residual volume excluding nodules. Multivariate logistic regression analysis showed that female gender, higher BMI-adjusted thyroid volume and residual thyroid volume excluding nodules, nulliparity, age and fT3 increase the risk of developing nodules. Conclusions. These results demonstrate that adult thyroid tissue undergoes changes that are already detectable by US after almost six years. Half of the enrolled subjects developed de novo nodules or colloid cysts of poor clinical relevance.